(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Observations of the torsion balances` and the torsind`s behavior at the moments of the solar and lunar eclipses, the transit of Venus, the occultation of Venus by the Moon were performed. It is shown that in the most cases the devices reaction to these phenomena either outstripped or lagged behind the actually observed phenomenon. The statement is substantiated that the torsind reacts to non-electromagnetic radiation of an unknown nature, arising in the outer space surrounding the Earth.